The late Silurian–Middle Devonian long-term eustatic cycle as a possible control on the global generic diversity dynamics of bivalves and gastropods - Ruban, Dmitry A. (Geologos, 2013)
A long-term eustatic cycle (fall and subsequent rise of the global sea level) embraced the late Silurian-Middle Devonian time interval. Potentially, these sea-level changes could drive global biodiversity. The stratigraphic ranges of 204 bivalve genera and 279 gastropod genera included into the famous Sepkoski database allow reconstructing changes in the total diversity and the number of originations and extinctions of these important groups of marine benthic macro- -invertebrates during this interval. None of the recorded parameters coincided with the long-term global sea-level cycle. It cannot be not excluded, however, that the global sea-level changes did not affect the regions favourable for bivalve and gastropod radiation because of regional tectonic mechanisms; neither can it be excluded that the eustatic control persisted together with many other extrinsic and intrinsic controls. Interestingly, the generic diversity of gastropods increased together with a cooling trend, and vice versa. Additionally, the Ludlow, Eifelian, and Givetian biotic crises affected, probably, both fossil groups under study. There was also a coincidence of the relatively high bivalve generic diversity, initial radiation of gastropods and the entire biota, and the diversification of brachiopods with the Early Devonian global sea-level lowstand, and this may be interpreted as evidence of a certain eustatic control on the marine biodiversity.